Effect of Cutaneous Heat Pain on Corticospinal Excitability of the Tibialis Anterior at Rest and during Submaximal Contraction - Maxime Billot; Cécilia Neige; Martin Gagné; Catherine Mercier; Laurent J. Bouyer (Neural Plasticity)
Previous studies have shown that pain can interfere with motor control. The neural mechanisms underlying these effects remain largely unknown. At the upper limb, mounting evidence suggests that pain-induced reduction in corticospinal excitability is involved. No equivalent data is currently available at the lower limb. The present study therefore examined the effect of thermal pain on the corticospinal drive to tibialis anterior (TA) at rest and during an isometric submaximal dorsiflexion. Transcranial magnetic stimulation was used to induce motor-evoked potentials (MEPs) in the TA at rest and during contraction in the presence or absence of cutaneous heat pain induced by a thermode positioned above the TA (51°C during 1 s). With similar pain ratings between conditions (3.9/10 at rest and 3.6/10 during contraction), results indicate significant decreases in MEP amplitude during both rest (−9%) and active conditions (−13%) (main effect of pain, p=0.02). These results therefore suggest that cutaneous heat pain can reduce corticospinal excitability in the TA muscle and that such reduction in corticospinal excitability could contribute to the interference of pain on motor control/motor learning.